Mysteries of the 1477 Presentation Miniature and Shakespeare’s Richard III - Natalia E. Mikeladze (Studia Litterarum)
Presentation miniature is a particular genre of medieval illustration for illuminated manuscripts, which has the value of a document and brought many portraits of historical figures. The article is devoted to the study of presentation miniature in the manuscript (MS 265 Library of Lambeth Palace, London) dated December 1477. It reproduces ceremony of presenting the book The Dictes and Sayings of the Philosophers by Anthony Woodville, Earl Rivers, to the family of Edward IV. The book has been translated earlier by Earl Rivers and published by William Caxton in November of the same year. The miniature contains riddles and raises many questions. They concern the identification and specification of persons depicted in the miniature: the figure in black (who for a long time was seen as the printer Caxton or the scribe); the king’s relative in ermine; figures in red, blue and green (hypothetically identified by us with famous historical figures whose portraits have not reached our days). The study of an interior detail (a door or a mirror?) and its role in the composition of the illustration gives rise to an original hypothesis and calls into question the dating of the miniature. Finally, the established history of possession of a manuscript in Shakespeare’s time does not exclude the playwright acquaintance with it and its influence on the image of the kingvillain Richard III. The article attempts to clarify identified mysteries of the miniature and argue emerged hypotheses.